Increased carbohydrate availability effects energy and nutrient periodisation of professional male athletes from the Australian Football League - Salagaras, B. S.; Mackenzie-Shalders, K. L.; Slater, G. J.; McLellan, C.; Coffey, V. G. (Applied Physiology, Nutrition, and Metabolism, 2021)
This research aimed to explore the effect of increased carbohydrate availability intervention on energy intake and distribution in professional Australian Football athletes. Six 24-h energy and macronutrient intakes were quantified (n = 19 males; age 24 ± 4 y, stature 187 ± 8 cm, mass 87 ± 9 kg) using photographic food diaries and Foodworks analyses. Energy expenditure was estimated for the same period using GeneActiv accelerometers. During 3 control days, athletes had ad libitum access to food, while the 3 intervention days increased carbohydrate availability, through greater prompting and access to carbohydrate foods. Daily energy intake was higher during intervention (185 ± 40 kJ/kg/d) compared with control (172 ± 31 kJ/kg/d; p < 0.05) but remained below estimated expenditure, and carbohydrate intake was also greater with intervention (5.0 ± 0.2 g/kg/d) than control (4.0 ± 0.2 g/kg/d; p < 0.05). Expenditure was highest during the morning, which coincided with lowest intake on all days, while the intervention was associated with greater carbohydrate intake in the morning (0.6 g/kg, p < 0.05) compared with control. Increasing availability of carbohydrate during high-load training generated a modest increase in carbohydrate and energy intake, and the intervention was most effective in improving carbohydrate intake during mornings. Novelty: • Increased access and provision of carbohydrate foods increased carbohydrate consumption and energy intake on high training load days. • Daily distribution of energy intake can be modified through actively promoting carbohydrate consumption.